2019
DOI: 10.3390/polym11111822
|View full text |Cite|
|
Sign up to set email alerts
|

Design of Web-to-Web Spacing for the Reduced Pressure Drop and Effective Depth Filtration

Abstract: The study aims at lowering the pressure drop and extending the service life at a given set of filter materials implementing a space between the filter layers. As design factors, the web-to-web space was implemented by inserting either a bulk air gap or porous spacer web between the filter webs. The effect of spacing, either by the air gap or by the spacer web, on the pressure drop reduction was apparent for 4-layer constructions, and the effect was greater at the higher face velocity. The use of spacer web was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 48 publications
(51 reference statements)
0
15
0
Order By: Relevance
“…It has been demonstrated that the exposure of an electret filter to heat, humidity, and solvent can cause deterioration of filtration performance, as a result of charge loss [17,22,24].The environmental factors that deteriorate the electret filtration have been studied rather frequently [8,17,18,24], probably because it is associated with the practical use conditions; on the other hand, the material aspects that influence the charge decay have rarely been studied. While various material options were examined to attain the high-quality factor filters [10,25,26], it lacked scrutiny on the material attributes that enable the long-term charge retention. Moreover, the dielectric constant (ε r ) of material has rarely been associated with the charge decay phenomenon in experimental investigation [1,27], while there are implications that ε r is related with the charge stability and conductivity [7,27,28].The purpose of this work is to investigate the polymeric attributes that influence the charge retention capacity of electret filters.…”
mentioning
confidence: 99%
“…It has been demonstrated that the exposure of an electret filter to heat, humidity, and solvent can cause deterioration of filtration performance, as a result of charge loss [17,22,24].The environmental factors that deteriorate the electret filtration have been studied rather frequently [8,17,18,24], probably because it is associated with the practical use conditions; on the other hand, the material aspects that influence the charge decay have rarely been studied. While various material options were examined to attain the high-quality factor filters [10,25,26], it lacked scrutiny on the material attributes that enable the long-term charge retention. Moreover, the dielectric constant (ε r ) of material has rarely been associated with the charge decay phenomenon in experimental investigation [1,27], while there are implications that ε r is related with the charge stability and conductivity [7,27,28].The purpose of this work is to investigate the polymeric attributes that influence the charge retention capacity of electret filters.…”
mentioning
confidence: 99%
“…[ 20 ] We chose ≈10 2 µm coarse filter because conventional high‐efficiency filters (like nanofibrous filters) with a high packing density have a very high air resistance, low dust‐holding capacity, and early clogging. [ 17,35–37 ] We believe that coarse filters with large pores would promote in‐depth filtration, maintaining a lower air resistance with the continued PM accumulation.…”
Section: Resultsmentioning
confidence: 99%
“…For the solid aerosol, the loading trends can differ by the filter characteristics. For the porous electret filter that allows depth loading, penetration initially increases as the charged surface is masked by the deposition of solid particles; then after reaching the maximum penetration, the penetration begins to decrease as the solid particles clog the pores of the filter material [ 30 , 31 , 32 ]. The resistance may build up more quickly after reaching the maximum penetration, as the pores of the filter are clogged.…”
Section: Filtration Performance Of Fiber-based Filters For Particumentioning
confidence: 99%
“…Electrospun nanofibers can be advantageous for capturing small particles due to their high specific surface area and the inherent initial charges resulting from the electric field-driven process. However, nanofibers with a high packing density may result in a high resistance that leads to an earlier clogging [ 30 , 31 , 97 , 106 ]; thus, design parameters including fiber size, solidity, thickness, and basis weight should be prudently chosen to satisfy both filtration efficiency and resistance.…”
Section: Fibrous Assembly For Advanced Filtrationmentioning
confidence: 99%
See 1 more Smart Citation